Proteinase PrtP impairs lactococcin LcnB activity in Lactococcus lactis BGMN1-501: new insights into bacteriocin regulation - Vukotic, Goran; Mirkovic, Nemanja; Jovcic, Branko; Miljkovic, Marija; Strahinic, Ivana; Fira, Djordje; Radulovic, Zorica; Kojic, Milan (Frontiers in Microbiology, 2015)
Proteinases and bacteriocins are of great importance to the dairy industry, but their interactions have not been studied so far. L. lactis subsp. lactis BGMN1-5 is a natural isolate from homemade semi-hard cheese which produces two bacteriocins (Lactococcin B and LsbB), as well as proteinase PrtP. A medium-dependent increase in the bacteriocin LcnB activity of Lactococcus lactis BGMN1-501, a derivate of L. lactis subsp. lactis BGMN1-5, was shown to be accompanied by a decrease in its promoter activity. A similar effect of media components on gene expression was reported for proteinase PrtP, whose gene is co-localized on the same plasmid as the lcnB gene. Thus, the PrtP-LcnB interplay was investigated. Single gene knockout mutants were constructed with disrupted prtP or lcnB genes. PrtP– mutants showed higher bacteriocin activity that had lost its growth medium dependence, which was in contrast to the original strain. When LcnB from this mutant was combined with proteinase from the LcnB– mutant in vitro, its activity was rendered to the original level, suggesting that proteinase reduces bacteriocin activity. We propose a new model of medium dependent expression of these genes with regard to the effects of their interaction in vivo.